The Methodology of Stress Tests for the Kazakh Banking System - Natalia Podlich; Didar Illyasov; Elena Tsoy; Shynar Shaikh (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
In this paper, we describe the results for the section Stress Testing Methodology forKazakh Banking System which is part of the Development of an Early Warning Systemfor Kazakhstan project. The participating Kazakh institutions are the National Bank ofKazakhstan (NBRK), the Financial Supervisory Agency (FSA) and the National AnalyticalCentre of the Government and the National Bank of Kazakhstan (NAC). In this section,we apply different methodologies for developing stress testing tools for the Kazakhbanking system: the bottom-up and top-down approaches. The bottom-up approachis based on questionnaires we have transmitted to Kazakh banks asking them to calculatetheir own risk positions under stress. The collected results and the analyses show thatbanks tend to underestimate the decline in real estate prices and to overestimate currencydevaluation. In the top-down approach, we apply methodologies for portfolio andmacro stress tests to raw data collected by FSA and estimate the impact of the externalmacroeconomic shocks on the expected losses of financial institutions. In the portfoliostress test, the change in the expected losses under stress ranges between 34 percent and86 percent relative to the unconditional expected losses. In the macro stress test, we findan average change of 26 percent in the ratio of bad loans to total loans under stressscenario 1 and an average change of 80 percent under scenario 2 relative to the baselinescenario.
Keywords: 330; Bankensystem; Bankrisiko; Frühwarnsystem; Szenariotechnik; Kasachstan